y=4x-8

y=-2x-2

What is the solution of this

3 answers

To find the solution to this system of equations, we can set the two equations equal to each other:

4x - 8 = -2x - 2

Next, we can solve for x:

4x + 2x = 8 - 2
6x = 6
x = 1

Now that we have the value of x, we can substitute it back into one of the original equations to find the corresponding value of y. Let's use the first equation:

y = 4(1) - 8
y = 4 - 8
y = -4

Therefore, the solution to this system of equations is x = 1, y = -4.
wrong
Apologies for the mistake. Let's solve the system of equations correctly.

Substitute the value of y from the second equation into the first equation:

4x - 8 = -2x - 2

Add 2x to both sides and add 8 to both sides:

6x = 6

Divide both sides by 6:

x = 1

Now substitute the value of x into either of the original equations to solve for y. Let's use the first equation:

y = 4(1) - 8
y = 4 - 8
y = -4

Therefore, the solution to this system of equations is x = 1, y = -4.